The secret language of stones : a novel - Rose, M. J., 1953- (Atria Books, 2016)
In World War I Paris, Opaline Duplessi, an employee at the famous La Fantasie Russie jewelry store, spends her time making trench watches for soldiers at the front, and mourning jewelry for the mothers, wives, and lovers of those who have fallen. People say that Opaline's creations are magical, a word she would rather not use. But she does have a rare gift, a form of lithomancy that allows her to translate the energy emanating from the stones and receive messages from beyond the grave. In her mind, she is not a mystic, but merely a messenger, giving voice to soldiers who died before they were able to properly express themselves to loved ones. Until one day, one of these fallen soldiers communicates a message directly to her, and Opaline sets off on a journey into the darkest corners of wartime Paris and across the English Channel, where the exiled Romanov dowager empress waits to discover the fate of her family. --